Jean Jaurès : neutralité, religion, socialisme et école laïque - Jean-Marc Lamarre
In his papers about educational neutrality, Jaurès stresses that neutrality is a lie and that the Church as well as conservative republicans are seeking by this means to thwart the emancipatory nature of public education : "only the nothingness is neutral". Jaurès upholds a republican and socialist secularity. Secularity is emancipation and socialism is the end state of the emancipatory process which arose with the French Revolution. Nevertheless, how can the teacher commit himself for socialism while respecting the secularity principle and the pupil's freedom of conscience ? "Only what we are is taught and can be taught'' states Jaurès. Socialism is not a doctrine that the schoolmaster can teach, but is the life principle enlivening his teaching. Jaurès recommends a pedagogic method formed simultaneously with objectivity, enthusiasm, width and perspective. The teacher moves himself aside facts and commits himself with euphoria for the progress of humankind. He expands his teaching to all major problems and raises the child's mind toward its embodied awareness of infinity.